Psychometric properties of the Teachers’ Sense of Efficacy Scale in a sample of Chilean public school teachers - Gálvez-Nieto, José Luis; Salvo-Garrido, Sonia; Domínguez-Lara, Sergio; Polanco-Levicán, Karina; Mieres-Chacaltana, Manuel (Frontiers in Psychology, 2023)
The Teachers' Sense of Efficacy Scale (TSES) has demonstrated suitable levels of reliability and validity for its use on the teacher population in several countries, and it is the most used scale to assess teachers' beliefs in their efficacy. However, few psychometric studies exist on its applicability to elementary teachers in public schools. This study analyzed the psychometric properties of the TSES in teachers who work in elementary education. The sample comprised 1406 Chilean teachers, mainly women (77.2%), from various Chilean public and subsidized schools. The results obtained from three confirmatory factor analyses demonstrated that the model that best fit the data was bifactor exploratory structural equation modeling (B-ESEM) for 24 items, one general factor, and three residual factors. The results of the factorial invariance analysis indicate that the TSES remains stable up to the strict level of invariance for the variable sex. These results imply that the TSES can be used on Chilean teachers. The results are discussed based on the theoretical and empirical evidence available.